Conceptual Model for Adoption Cloud-Based ERP in SMEs: Case Study Iraq - Jaafar Mohammed, Ghaith; Burhanuddin, MA (International Journal of Engineering and Technology, 2018)
Cloud based Enterprise Resource Planning (ERP) frameworks showed up the responses to every one of the issues looked customary ERP framework. Versatility, adaptability, and cost proficiency. Fast sending and low forthright ventures are its highlights. Cloud based ERP goes about as a substitute to on-premises ERP frameworks. The execution of cloud-based ERP framework is looked with numerous impediments. The usage of ERP framework is exceptionally perplexing, dreary, and tedious and a gigantic need of progress is produced in ERP structure to improve ERP frameworks foundation and usefulness. The built up nations' SMEs have officially executed cloud-based ERP. Be that as it may, then again, the cloud-based ERP usage is extremely constrained and relatively few examinations have been done dependent on it. This present paper's motivation is to explore the issues that impact the cloud-based ERP reception in Iraq SMEs. Also, different elements will be inspected by us that influence the cloud-based ERP appropriation in various SMEs in Iraq by consolidating Technology-Organization-Environment (TOE) system and Diffusion of Innovation hypothesis. Proposals of future work research will likewise be given.